Assessing the Effect of Chromolaena odorata on Maize (Zea mays L.) Growth and Yield in the Semi-Deciduous Forest Zone of Côte d’Ivoire - Roger Bayala; Lisette Zeh Tokpa; Firmin Kouamé Konan; Kouamé Emile Ange Jr. Brou; Ambroise Casimir Laopé Siene; Pauline Amanko Ndouba; Nathanael A. Bogie; Sabas Sadaiou Yao Barima (Journal of Tropical Crop Science, 2026)
Chromolaena odorata is a dominant pioneer species in the successional vegetation following deforestation in humid and sub-humid tropical regions. Despite its prevalence, the specific interactions between C. odorata and subsequent food crops remain poorly characterized. This study aimed to evaluate the influence of C. odorata on the growth and yield of maize (Zea mays L.) under varying nutrient regimes. The experiment employed a randomized complete block design to assess the interaction between shrub presence (present vs. absent) and fertilization (0 or 1× the recommended N–P–K rate). The results indicated that the presence of C. odorata significantly increased maize height, stem diameter, and leaf count after anthesis. Furthermore, under high-rainfall conditions, C. odorata significantly increased grain yield and yield components. During the long rainy season, grain yields ranged from 8.75 to 10.74 ton/ha in plots integrated with C. odorata, compared to 7.63 to 7.84 ton/ha in monoculture plots. These agronomic advantages suggest that C. odorata improves productivity through non-thermal biomass management, likely by stabilizing soil pH. Notably, total nitrogen, available phosphorus, cation exchange capacity (CEC), and organic carbon content remained stable across the 0–20 cm and 20–40 cm soil profiles.